The Impact Of Cost Accounting Information On Company Performance: An Exploratory Study In Iraq - Laith Noman Hassoon (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The paper aimed to test the role of cost accounting information in feeding and guiding administrative decision makers in a way that contributes to enhancing the overall performance of the company. As the internal information provided by cost accounting works to clarify the strengths and weaknesses in detail within the company’s organizational structure, allowing management to gain a broader perspective. And more accurate in the areas of improving the company's performance. Cost accounting information has been identified in two categories: planning information and control information, while the company's performance has been identified in terms of productivity, cost reduction control, and profitability. The paper community has been represented by accountants working in a number of Iraqi industrial companies. A questionnaire form was prepared by the researcher to achieve the purpose of collecting the data necessary to measure the research variables, in accordance with the descriptive analytical approach adopted in the current research. The number of questionnaires retrieved and suitable for analysis reached 72 forms. The research reached a number of conclusions, the most important of which is that accounting information Costs enhance the efficiency and effectiveness of companies, which contributes to maximizing the company's performance. Given the stability of this positive effect, it follows that there is a need to increase attention to the quality of cost accounting information and the scope of its production in companies. This information contributes to reaching a more accurate measurement of the cost of the product and thus contributes to determining more competitive prices.